Modulation of Lactobacillus plantarum gastrointestinal robustness by fermentation conditions enables identification of bacterial robustness markers. - Hermien van Bokhorst-van de Veen; I-Chiao Lee; Maria L Marco; Michiel Wels; Peter A Bron; Michiel Kleerebezem (PLoS ONE, 2012)
BACKGROUND: Lactic acid bacteria (LAB) are applied worldwide in the production of a variety of fermented food products. Additionally, specific Lactobacillus species are nowadays recognized for their health-promoting effects on the consumer. To optimally exert such beneficial effects, it is considered of great importance that these probiotic bacteria reach their target sites in the gut alive. METHODOLOGY/PRINCIPAL FINDINGS: In the accompanying manuscript by Bron et al. the probiotic model organism Lactobacillus plantarum WCFS1 was cultured under different fermentation conditions, which was complemented by the determination of the corresponding molecular responses by full-genome transcriptome analyses. Here, the gastrointestinal (GI) survival of the cultures produced was assessed in an in vitro assay. Variations in fermentation conditions led to dramatic differences in GI-tract survival (up to 7-log) and high robustness could be associated with low salt and low pH during the fermentations. Moreover, random forest correlation analyses allowed the identification of specific transcripts associated with robustness. Subsequently, the corresponding genes were targeted by genetic engineering, aiming to enhance robustness, which could be achieved for 3 of the genes that negatively correlated with robustness and where deletion derivatives displayed enhanced survival compared to the parental strain. Specifically, a role in GI-tract survival could be confirmed for the lp_1669-encoded AraC-family transcription regulator, involved in capsular polysaccharide remodeling, the penicillin-binding protein Pbp2A involved in peptidoglycan biosynthesis, and the Na(+)/H(+) antiporter NapA3. Moreover, additional physiological analysis established a role for Pbp2A and NapA3 in bile salt and salt tolerance, respectively. CONCLUSION: Transcriptome trait matching enabled the identification of biomarkers for bacterial (gut-)robustness, which is important for our molecular understanding of GI-tract survival and could facilitate the design of culture conditions aimed to enhance probiotic culture robustness.